A musa da paisagem: uma etnografia da duração sobre a memória ambiental de Carolina-MA - CRUZ, Rafael de Oliveira (2023)
In this etnographic research, I seek to present the landscape of Carolina-MA as cultural heritage that anchors the identity and the collective memory of the community that lives there. Revealing different aspects of landscape of Carolina (its urbanity, tourist atractions and sociability), I demonstrate the urgente need for continuity of public-private articulations that allowed the recognition of the heritage and cultural assets of this locality, witch still holds others the desserves due attention. During the fieldwork, observations were made (direct, participant, floating) witch involved visitis to Historical Center, museum, resorts and sightseeings in the municipality, places in witch interactions between researcher and interlocutors obeyed specific criteria for each situation. Social media were also very important space for interaction and observation the narratives and imagens shared about Carolina-MA. A bibliographic research was also carried out in order to contextualize the observed social scenario. Finally, the research presents the landscape as a manifestation of the relationship between nature and society, in permanent reciprocal influence.